Roles of education in creating awareness of sustainability campus management for green campus concept - Rusli, Nazrul; Mohd. Hussain, Mohd. Ramzi; Nizarudin, Norhanis Diyana; Sabri, Syikh Sazlin Shah; Abdul Hamed, Sapiah (Asian Scholars Network, 2023)
This paper examines the role of education in creating awareness about sustainable campus management and the green campus concept. By involving the entire campus community, sustainable campus initiatives can lead to a more vibrant and inclusive community. A green campus is one that is environmentally responsible and promotes the sustainability of the campus environment. Educating students, educators, and non-academic staff about sustainability campus management and the green campus concept can encourage sustainable lifestyle choices and increase environmental awareness. This can foster a culture of sustainability and create a more environmentally conscious community. When universities and colleges implement sustainable campus management practices and principles, it is referred to as the green campus concept. Education awareness is a characteristic that is integral to an individual or entity and helps identify or define them. Sustainable campus management involves designing, implementing, and overseeing sustainable practices and activities such as integrating sustainability concepts into transportation, infrastructure, facilities management, resource conservation, waste management, and curriculum creation. A green campus is one that prioritizes the environment and incorporates environmental science into its administration, policy, and academic pursuits. By educating the campus community about the green campus concept and sustainability campus management, it is hoped that a sustainable understanding will be fostered, leading to a bright future for the green campus initiative. For the adaptation value toward sustainability campus management for green campus concept sustainable for the campus community.